ENGINEERING GEOLOGICAL AND GEOTECHNICAL INVESTIGATION OF LANDSLIDE EVENTS IN WILDFIRE AFFECTED AREAS OF ILIA PREFECTURE, WESTERN GREECE - Depountis, N.; Lainas, S.; Pyrgakis, D.; Sabatakakis, N.; Koukis, G. (Bulletin of the Geological Society of Greece, 2010)
In August 2007 Ilia Prefecture suffered one of the most devastating wildfires that have ever happened on European level. Approximately 870km2 , mainly forest and agricultural land, were lost, more than 60 people were killed, hundreds were injured and many villages suffered extensive damage. Heavy rainfall and human activities, favoured by the loss of vegetation and the overall susceptibility of geological formations in landsliding, induced the manifestation or reactivation of various scale landslide phenomena. In order to investigate and mitigate the problem University of Patras was commissioned by the Region of Western Greece to undertake an Engineering Geological and Geotechnical investigation. Site investigation accomplished in seven municipalities focusing on several landslide events with serious socio-economic impact and as a result many small scale cases were identified. In each one of these cases large scale engineering geological mapping was conducted and remedial and protection measures were designed.